Inhibition of semicarbazide‐sensitive amine oxidase/vascular adhesion protein‐1 reduces lipopolysaccharide‐induced neuroinflammation. (10th June 2017) - Becchi, Serena; Buson, Alberto; Foot, Jonathan; Jarolimek, Wolfgang; Balleine, Bernard W
Abstract : Background and Purpose: Neuroinflammation is initiated by a variety of stimuli including infections, sepsis, neurodegenerative diseases or traumatic brain injury and, if not adequately controlled, can lead to various degrees of neuronal damage and behavioural impairment. A critical event in the initial steps of inflammation is neutrophil extravasation. Semicarbazide‐sensitive amine oxidase (SSAO, also known as vascular adhesion protein 1 or VAP‐1) regulates neutrophil adhesion and extravasation. Here, we elucidate the role of SSAO/VAP‐1 in the early stage inflammatory response after LPS insult in the brain. Experimental Approach: PXS‐4681A, a selective and irreversible SSAO/VAP‐1 inhibitor, was tested in two rat models of neuroinflammation, following systemic or i.c.v. LPS. Immunohistochemical and immunofluorescence techniques were used to measure neutrophils and microglia. VAP‐1 was quantitated by Western blotting. Key Results: Both systemic and i.c.v. administration of LPS induced an increase in neutrophil recruitment and microglial response in various brain areas including the substantia nigra and striatum. PXS‐4681A produced a significant inhibition of neutrophil recruitment and extravasation after i.c.v. LPS injection and also reversed microglial cell recruitment and morphological changes to the level of the sham controls in both LPS models. Conclusions and Implications: PXS‐4681A acted as an effective anti‐inflammatory agent after both systemic and i.c.v. LPS injections suggesting that SSAO/VAP‐1 inhibition could be beneficial in the treatment of brain inflammation.